Residual Radioisotopes Generated from Neutron Irradiated Aluminum Capsules - Imam Kambali; Indra Saptiama; Hari Suryanto (Aceh International Journal of Science and Technology, 2017)
Aluminum (Al) is often used to house a molybdenum oxide (MoO3) target for neutron or proton-produced technetium-99m (99mTc) radioisotope. During neutron or proton bombardment of an Al body, residual radioisotopes could be generated following nuclear reactions between the incoming particles and the Al body. In this research, residual radioisotopes produced following nuclear reactor based-neutron irradiation of Al body were experimentally measured using a portable gamma ray spectroscopy system; whereas TALYS 2015 calculated data were used to evaluate various nuclear reactions for the by-product identification. As a comparison, Al body used in a cyclotron-based 99mTc production was also analyzed. Experimental data indicated that relatively long-lived radioisotopes such as 26Al, 22Na and 24Na were identified in the Al body following nuclear reactor-based 99mTc production, whereas the presence of 27Mg radioisotope was, for the first time, experimentally detected in both the Al bodies for nuclear reactor-based and cyclotron-based 99mTc production. A special safety attention should be paid to the radiation workers when producing 99mTc using a nuclear reactor since it generates 26Al (half life = 716,600 years).